Internet use among urban Malaysians: Network diversity effects - Rycker, Antoon De; Yang, Nicole Yang Lai; Lee, Cheng Ean Catherine *; Ramachandran, Ponnan (2016)
This study examines social network diversity in urban areas relative to residents’ usage of information and communication technologies (ICTs). Individual-level variation in social network diversity was measured using position generator data collected as part of a survey conducted in Malaysia’s Klang Valley (N = 808). Regression analyses were performed to assess the extent to which network diversity is related to ICTs. We find that most ICTs have a negative effect on diversity. Only frequent use of the Internet at work, mobile access to the Internet, and reading online news or blogs contribute positively to diversity. Findings support both a tendency toward ‘networked individualism’ and the more recent ‘glocalization’ thesis that some ICTs may also afford participation within local space rather than only across distant space.